Comprehensive geriatric assessment of risk factors associated with adverse outcomes and resource utilization in cancer patients undergoing abdominal surgery. Issue 3 (26th June 2013) - Badgwell, Brian; Stanley, Jordan; Chang, George J.; Katz, Matthew H.G.; Lin, Heather Y.; Ning, Jing; Klimberg, Suzanne V.; Cormier, Janice N.
Abstract Background The purpose of this prospective study was to identify risk factors for adverse outcomes or increased resource utilization after abdominal cancer surgery in geriatric patients. Methods Baseline clinical and geriatric assessment variables including functional status, nutritional status, comorbidity index, mental status, depression scale score, fatigue inventory scale, and polypharmacy scale were prospectively recorded for patients age ≥65 undergoing intra‐abdominal oncologic surgery. Outcome variables included morbidity, mortality, discharge to nursing facility, prolonged hospital stay, and readmission. Results Of 111 patients, surgery type was colorectal in 40%, hepatopancreatobiliary in 30%, and gastric/duodenal in 14%. Variables associated with discharge to a nursing facility on multivariate analysis included weight loss ≥10% (OR 6.52 [95% CI: 1.43–29.76], P = 0.02), ASA score ≥2 (OR 5.08 [1.13–22.77], P = 0.03), and ECOG score ≥2 (OR 4.51 [1.03–19.71], P = 0.04). Variables independently associated with prolonged hospital stay included weight loss ≥10% (OR 4.03 [1.13–14.43], P = 0.03), the presence of polypharmacy (OR 2.45 [1.09–5.48], P = 0.03), and distant disease (OR 0.37 [0.15–0.91], P = 0.03). No variables were associated with morbidity or readmission. Conclusions Pre‐operative clinical and geriatric assessment tools can help predict the need for discharge to a nursing facility or increased length of stay. Future studies will be required to identify patients suitable for interventions to decrease hospital and post‐discharge resource utilization. J. Surg. Oncol. 2013; 108:182–186. © 2013 Wiley Periodicals, Inc.